Debt Trapped: Analysing the Impact of IMF on Economic Growth and Human Development in Highly Indebted Countries, with a Focus on Corruption - Salman, Doaa M. Salman; El-Ahmar, Ahmed Adel; Youssri, Dina; Klose, Jens (Ekonomika, 2025)
Being indebted represents significant risks associated with global financial instability in a world where financial stability hangs precariously between debt and economic growth. The International Monetary Fund (IMF) casts a critical eye over countries navigating the perilous seas of fiscal responsibility, aiming to improve their economic performance. Hence, evaluating the connection between IMF loans and sustainable growth in highly indebted countries is crucial. This study aims to examine the impact of IMF loans on real GDP and human development in a panel of the 13 most indebted countries from 1997 to 2020, by using pooled OLS and fixed-effect estimators. The article contributes to the existing literature in two ways. On the one hand, a broad set of human development indicators is analysed. On the other hand, corruption is incorporated into the analysis, explicitly measuring the simultaneous effects of IMF loans and corruption. It has been found that IMF loan growth tends to lower GDP growth, human development, and mortality. IMF loans often come with conditions that may lead to austerity measures. While these measures can negatively impact economic growth in the short term, they might also redirect resources toward social programs which improve health outcomes, thereby reducing mortality rates. When corruption is considered, a reduction in corruption leads to more effective IMF loans, increased human development, and decreased mortality even further. Therefore, it is recommended that IMF loans should always be accompanied with incentives to reduce corruption.